Waking up from the American dream: on the experience of young Americans during the housing boom of the 2000s - Luc Laeven; Alexander Popov (European Central Bank (ECB), 2016)
We exploit regional variations in house price fluctuations in the United States during the early to mid-2000s to study the impact of the housing boom on young Americans' choices related to home ownership, household formation, and fertility. We also introduce a novel instrument for changes in house prices based on the predetermined industrial structure of the local economy. We find that in MSAs which experienced large increases in house prices between 2001 and 2006, the youngest households were substantially less likely to purchase residential property, to be married, and to have a child, both in 2006 and in 2011.
Keywords: E32; G21; J10; R21; 330; credit constraints; fertility; home ownership; house prices; household formation